2021
DOI: 10.3390/s21165255
|View full text |Cite
|
Sign up to set email alerts
|

Star Sensor Denoising Algorithm Based on Edge Protection

Abstract: Single-pixel noise commonly appearing in a star sensor can cause an unexpected error in centroid extraction. To overcome this problem, this paper proposes a star image denoising algorithm, named Improved Gaussian Side Window Filtering (IGSWF). Firstly, the IGSWF algorithm uses four special triangular Gaussian subtemplates for edge protection. Secondly, it exploits a reconstruction function based on the characteristic of stars and noise. The proposed IGSWF algorithm was successfully verified through simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several denoising techniques have been developed recently to pre-filter the star images to preserve their shapes. Methodologies to ward off the interference of the background and enhance the star image-background contrast include the following: block adaptive threshold segmentation (BATS) [ 26 ], ring filter [ 27 ], hybrid filter [ 28 ], dark channel filter [ 29 ], and Improved Gaussian Side Window Filter (IGSWF) [ 30 ]. In the case of star sensors with small field-of-view (FOV), even muddled star image spots must be included in the attitude estimation process.…”
Section: Introductionmentioning
confidence: 99%
“…Several denoising techniques have been developed recently to pre-filter the star images to preserve their shapes. Methodologies to ward off the interference of the background and enhance the star image-background contrast include the following: block adaptive threshold segmentation (BATS) [ 26 ], ring filter [ 27 ], hybrid filter [ 28 ], dark channel filter [ 29 ], and Improved Gaussian Side Window Filter (IGSWF) [ 30 ]. In the case of star sensors with small field-of-view (FOV), even muddled star image spots must be included in the attitude estimation process.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al employed SWF for image-dehazing optimization, ensuring that texture and edge information was preserved [ 21 ]. Lu et al suggested an improved SWF algorithm for edge-preserving denoising filtering of star maps collected by in-orbit star-sensitive sensors to improve the star point localization accuracy [ 22 ]. The above-mentioned related studies revealed that SWF has both morphological and grayscale statistical properties, so it was used as an operator for morphological clustering of local pixels, allowing the hereby proposed binarization algorithm to consider both local grayscale distribution information and morphological information.…”
Section: Introductionmentioning
confidence: 99%